INDEPENDENT DOMINATION NUMBER OF GRAPHS THROUGH VERTEX SWITCHING - Parveen, S. Thilsath; Balamurugan, B.J (TWMS journal of applied and engineering mathematics, 2024)
Let G = (V, E) be a graph with vertex set V and edge set E. An independent dominating set S of G is a subset of V with the property that every vertex in V - S is adjacent to some vertex in S and no two vertices within S are adjacent. The number of vertices in a minimum independent dominating set in the graph G is called the independent domination number i(G) of G. In this article, the independent domination number of graphs obtained through vertex switching have been computed with appropriate illustration. Keywords: Graphs, independent domination, independent dominating set, independent domination number, vertex switching. AMS Subject Classification: 05C69, 05C76.